THEORETICAL ASPECTS OF STRATEGIC PLANNING OF A COMPANY'S FOREIGN ECONOMIC ACTIVITY - TIURINA, Nila; KARVATSKA, Nataliya; NAZARCHUK, TETYANA; PETYAK, ANDRII (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article deals with the issue of the need for strategic planning in the foreign economic activity of enterprises and substantiates its relevance.  The essence, types, purpose, content of the planning process in the field of foreign economic activity are considered. The opinion of various authors regarding the content of the components of the planning process has been analyzed. The interpretation of the concept of "strategy" by different authors is considered, the peculiarities, commonality of opinions and the possibility of adapting the mentioned concept to foreign economic activity are determined.  The author's definition of the concept of "foreign economic strategy of the enterprise" was formed.  Approaches to the formation of the strategic profile of enterprises in international business are analyzed. Strategic planning is considered as an organizational embodiment of the strategy of foreign economic activity.  The phasing and content of the process of forming a strategy for the development of the enterprise's foreign economic activity have been determined. A list and a brief description of possible strategies for the use of foreign economic activity have been created. The conclusions of the research were drawn and the prospects for further research were determined.
Keywords: foreign economic activity; planning; strategy; management